Pengaruh konseling gizi terhadap status gizi ibu hamil KEK pada program JPS-BK di Kota Palembang - Hana Yuniarti; Dradjat Boediman; Toto Sudargo (Jurnal Gizi Klinik Indonesia, 2005)
Background: Low quality and quantity of food and limited knowledge on nutrition are major cause of malnutrition among pregnant mothers. Nutrition counseling is expected to improve nutrition status of pregnant mothers.Objective: To identify the effect of nutrition counseling to nutrition status of chronic energy malnourished pregnant mothers.Method: The study was a quasi experiment which used pretest – posttest control group design. Subject of the study were pregnant mothers with upper arm circle < 23.5 cm. The study was conducted at 2 health centers which had high prevalence of chronic energy malnourished pregnant mothers in Palembang Municipality. Nutrition counseling was given every 2 weeks within 3 months. Data obtained were food consumption every 2 weeks at 6 times (multiple recall), weight gain and measurement of upper arm circle once a month and knowledge of the subject about nutrition.Results: There was difference in knowledge of mothers who got nutrition counseling from those who did not (p<0.05). There was difference in energy consumption of mothers who got nutrition counseling from those who did not (p<0.05). There was no difference in protein consumption between mothers who got nutrition counseling and those who did not (p<0.05). There was difference in weight and upper arm circle of mothers who got nutrition counseling and those who did not (p<0.05).Conclusion: Nutrition counseling affected increase of knowledge, energy consumption, weight and upper arm circle. Nutrition counseling did not affect increase of protein consumption.